ASSESSMENT OF THE ROAD IMPACTS ON CONIFEROUS SPECIES WITHIN THE ROAD-EFFECT ZONE USING NDVI ANALYSIS APPROACH - Gulci, Sercan; Akay, Abdullah Emin; Oguz, Hakan; Gulci, Nese (Parlar Scientific Publications (P S P), 2017)
Remote sensing (RS) techniques and Geographical information system (GIS) applications, which provide more economical and time saving methods than ground-based measurements, have been widely used for earth observation and environmental assessments. Thus, consider Landsat 7 Enhanced Thematic Mapper Plus (ETM+) images, the present and past conditions of the coniferous species and land change that are within 100 meters away from the road alignment were evaluated to explain the changes in the road effect zone. Normalized Difference Vegetation Index (NDVI) obtained from Landsat images of the years between 2000 and 2015 were performed by using thresholds to estimate temporal and spatial changes of the coniferous species. The value of thresholds (0.45<NDVI<0.65) for the NDVI reflections from healthy coniferous species have been taken into consideration in summer season. Binary classification was applied for NDVI reflection values of productive coniferous forests (PcF) and degraded coniferous forests (DcF), and then comparisons were performed to investigate temporal and spatial changes. The results investigated that approximately 18 % of the coniferous forests within the 100 m road buffer zone were turned into DcF. Beside beekeeping, grazing and social activities are defined as disturbances in research area. In conclusion, current roadside forestry applications and managements for road edges needs improved techniques and planning for sustainable management in forest road zones.
GULCI, Sercan/0000-0003-3349-517X
Keywords: Road-effect zone; Coniferous forests; Degradation; Landsat; Remote sensing; Sustainability